Text-to-speech vs. human voiced audio descriptions: a reception study in films dubbed into Catalan - Fernández Torné, Anna; Matamala, Anna (The Journal of Specialised Translation, 2015)
This article presents an experiment that aims to determine whether blind and visually impaired people would accept the implementation of text-to-speech in the audio description of dubbed feature films in the Catalan context. A user study was conducted with 67 blind and partially sighted people who assessed two synthetic voices when applied to audio description, as compared to two natural voices. All of the voices had been previously selected in a preliminary test. The analysis of the data (both quantitative and qualitative) concludes that most participants accept Catalan text-to-speech audio description as an alternative solution to the standard human-voiced audio description. However, natural voices obtain statistically higher scores than synthetic voices and are still the preferred solution.